Addition of Carrot Flour to Commercial Feed to Improve Colour Brightnees of Cupang Fish(Betta sp.) - Ansar, Ansar; Nasmia, Nasmia (AgriSains, 2021)
Bright colors are one of the main attractions of ornamental fish. The brighter the color of the ornamental fish, the higher the value. However, during the maintenance of ornamental fish, the color often becomes dull, the quality of the color decreases so that the ornamental fish is no longer attractive. Therefore, the color must be increased by one of the efforts by providing feed containing certain pigments. One of the efforts made to get evenly bright colors in the fish is feeding carotene sources and supplements. The purpose of this study was to determine the effect of adding carrot flour to commercial feed on the brightness level of Betta fish (Betta sp.). The study was conducted at the Laboratory of Water Quality and Aquatic Biology, Faculty of Animal Husbandry and Fisheries, Tadulako University from August-September 2020. The experimental design used Completely Randomized Design (CRD) with 5 treatments and 4 replications. Treatment A = without carrot flour, B = 48g, C = 50g D = 52g, E = 54g. The results obtained were that the addition of 54g carrot flour gave color enhancement to betta fish with an average score of 7,1.